A reconfiguração dos sujeitos da EJA no campo: o caso da EMEFM Mariano Ferreira de Nazareth - Reinholtz, Fernanda Rodrigues Neves (2019)
This work investigated the process of reconfiguration of the peasant subjects that access the Education of Young and Adults (EJA). It was sought to investigate the hypothesis that there is a deepening of the arrival of young people in the EJA, who had a regular course of schooling and who left school recently, including being migrated during the school year. To understand the phenomenon, we seek to know the construction of the concept of youth, assuming it in its multiplicity, abandoning the idea of a uniform group, taking it as a result of social relations, from the studies of Arroyo (2017), Dayrell (2007) and Pais (1990). From the perspective of the multiplicity of youth, this study analyzed the young peasants (CASTRO, 2005), who have sometimes not found conditions to remain in regular education and who have access to the EJA in an increasing way. He studied it in the field of educational policies (MAINARDES, 2017; 2018), using the Pluralist Epistemological Perspective (MAINARDES 2018). With this emphasis, the research involved the intersection of the fields of youth sociology, rural education and youth and adult education. This is a case study conducted at EMEFM Mariano Ferreira and Nazareth, in Domingos Martins / ES. The following were used as methodological instruments: the analysis of documents in the collection of EJA enrollment data in the school studied, the application of questionnaires and semi-structured interviews with 41 students and 10 teachers, as well as 7 directors from other teaching units in the municipality. The listening of the subjects made it possible to verify the aggravation of the process of migration and arrival of young people at EJA in two ways. In the voices of the majority of the young investigated, they are migrating of their own volition, due to the necessity of insertion in the world of work. When we listen to the directors and teachers we have that the students are being migrated as victims of an educational policy focused on raising indexes. Thus, the results indicate a need to revise the conception of EJA in the municipality, a modality for supporting those who did not have access to schooling at the "right age", to meet the needs of those who, even having access and regular schooling, without interrupting their trajectory, migrate or are being migrated to this modality characterizing a reconfiguration of the profile of the peasant students who arrive at EJA in Domingos Martins - ES with clear evidences that this phenomenon has its roots in the regular education.